1981
DOI: 10.1139/m81-033
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition activity and bacteriophage and bacteriocinlike particles associated with different species of Clostridium

Abstract: Thirty-four strains corresponding to 16 species of Clostridium were examined for growth inhibition activity and production of phage and bacteriocinlike particles. Twenty-five strains were found to inhibit growth of one or more of the other strains. The widest range of activity corresponded to C. bifermentans 18137 which inhibited growth of 23 strains. Cell-free filtrates of positive cultures were inactive with the exception of the one from C. bifermentans 18137. A wide variety of particles with diverse morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…The spirosomes consist of a left-handed helical structure about 6.5 nm in width, 12.5 nm in height and 11 nm in pitch, and its length ranges from 30 to 900 nm with a high frequency of 100 to 200 nm. Similar minute spirals have been observed in different species of Clostridium (15,17), Escherichia coli (6), and three species of Acholeplasma (8). Thus, spirosomes or similar spiral inclusions have been widely found in gram-positive and -negative bacteria.…”
Section: Superprecipitation-like Phenomenon and Destruction Induced Bsupporting
confidence: 76%
“…The spirosomes consist of a left-handed helical structure about 6.5 nm in width, 12.5 nm in height and 11 nm in pitch, and its length ranges from 30 to 900 nm with a high frequency of 100 to 200 nm. Similar minute spirals have been observed in different species of Clostridium (15,17), Escherichia coli (6), and three species of Acholeplasma (8). Thus, spirosomes or similar spiral inclusions have been widely found in gram-positive and -negative bacteria.…”
Section: Superprecipitation-like Phenomenon and Destruction Induced Bsupporting
confidence: 76%
“…Spirosomes were not found in the preparations from L. casei, E. coli, and Clostridium species by our weak sonication method but they were found in the preparations of cell lysates from L. casei and E. coli C as reported by some workers (5,6,9,11). Hence, the possibility that spirosomes exist in other "spirosome-absent" strains listed in Table 1 cannot be denied.…”
Section: Discussionsupporting
confidence: 57%
“…Ueda and Takagi (11) found similar spiral structures in mitomycin-induced lysates of Clostridium botulinu m type B. Kawata et al (6) found similar particles in the mesosomal fraction obtained from protoplasts of Lactobacillus fermenti and Lactobacillus casei by osmotic disruption and named the particle "spirosome." Since then, spirosomes or similar particles have been observed in both gram-positive and gram-negative bacteria (4,5,7,9). However their true origin and function are still obscure.…”
mentioning
confidence: 99%
“…A variety of bacteriophages, both lytic and lysogenic, have been described in different species of Clostridium [44,45] So far they have played only a very minor role in clostridial genetics, because no instances of transduction have been reported. Bacteriophages CA1 and HM3 of C. acetobutylicure have served as a valuable source of 'homologous' DNA for transfection of C. acetobutylicum protoplasts [32][33][34].…”
Section: Transductionmentioning
confidence: 99%